Law Enforcement on Tobacco Control and Smoking among Youths in the Northeast of Thailand (Indian Journal of Public Health Research & Development, 2020)
Thailand has imposed strong tobacco control policies to reducing smoking. The effectiveness of thosemeasures towards reducing smoking especially among youths still unknown. This study aimed to determinethe effectiveness of law enforcement on tobacco control among youth in the Northeast of Thailand. Thiscross-sectional study was conducted among 1,147 youths who were recruited by using a multistage randomsampling from 6 universities in the Northeast of Thailand. A self-administered structured questionnaire wasused to collect the data. The Generalized Linear Mixed Model was used to determine the association betweenlaw enforcement on tobacco control and smoking when controlling for other covariates. The results showthat 20.1% were current smokers. Law enforcement on tobacco control and smoking that were significantlyassociated with smoking among youths were had low level of awareness on tobacco raising price, antismokingcampaign, smoke-free in public areas, not showing pack, price and brand of cigarette at point ofsale product, pictorial health warnings and not distributing cigarette with tax avoidance/tax evasion. Theother covariates were male gender, alcohol drinker, had low level of attitude on not smoking, had smokersclose friend and had smoker father. One-fourth of youths in the Northeast of Thailand were current smokers.Legal measures had influence on youths’ smoking as well as gender, family and friends.
Keywords: Law enforcement, Smoking, Tobacco Control, Youths.